Hydraulics of water and nutrient application through drip irrigation- A review - KUMAR, MUKESH; KUMAR, ROHITASHW (Journal of Soil and Water Conservation, 2018)
Performance evaluation of irrigation system has been an important area of research for better management of water resources. This paper evaluated the application uniformity of water and nutrient through drip irrigation systems. To sustain the agricultural production we need to impress upon judicious use of water and nutrients by using proper water and nutrient management techniques including drip irrigation system which delivers the inputs directly to the root zone of the plants.The system operating pressure and drip-line length are the two important factors influencing the water and nutrients distribution uniformity in the field. The non-uniform application of water and fertilizers in field may lead to improper water and nutrients distribution within the soil profile along the drip-line length resulting in considerable reduction in crop yield and substandard quality of produce. Operating pressure in a micro-irrigation system is the main cause for non-uniform water and fertilizer distribution in the field and therefore, its effect needs to be studied and quantified This may also result in the groundwater contamination and soil degradation due to excessive leaching of nutrients from the crop root zone. Information about the water and nutrients movement and distribution patterns in the soil are of paramount importance for design of efficient fertigation systems. Drip irrigation can reduce exposure to water risks and input costs making an agribusiness operation more resilient, profitable and solvent. In this paper water and nutrient application uniformity for agricultural crops grown in different agro-climatic regions, are reviewed. Further, an effort has been made to compare the accuracy of various widely used methods results for application of water and nutrients under different climatic conditions.